2009
DOI: 10.4491/eer.2009.14.2.120
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Risk Assessment using E. coli in UV Disinfected Wastewater Irrigation on Paddy

Abstract: Water stress has become a major concern in agriculture. Korea suffers from limited agricultural water supply, and wastewater reuse has been recommended as an alternative solution. A study was performed to examine the effects of microorganism concentration in the ponded-water of a paddy rice field with reclaimed-water irrigation for evaluating the microbial risk to farmers and neighborhood children. Most epidemiological studies were performed based on an upland field, and they may not directly applicable to pad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…In fact, the use of wastewater for irrigation purposes can pose significant risks to farmers and more generally to the public health. There are many risk factors associated with the reuse of wastewater in irrigation such as the accumulation of the substances in soil voids which lead to a decrease in the crop growing, causing the microbe infection and soil deterioration [10]. The indirect reclaimed water reuse in irrigation occur when the cultivated land is far from the effluent source.…”
Section: Civil Engineering Department High Institute Formentioning
confidence: 99%
“…In fact, the use of wastewater for irrigation purposes can pose significant risks to farmers and more generally to the public health. There are many risk factors associated with the reuse of wastewater in irrigation such as the accumulation of the substances in soil voids which lead to a decrease in the crop growing, causing the microbe infection and soil deterioration [10]. The indirect reclaimed water reuse in irrigation occur when the cultivated land is far from the effluent source.…”
Section: Civil Engineering Department High Institute Formentioning
confidence: 99%
“…This means that additionally treated effluent after the regular WWTP processes meets the requirement for irrigation water [17]. However, when irrigating with treated wastewater diluted with stream water, the E. coli concentration exceeded the enteric disease risk value of 10´4, and this has been reported to cause infection to farmers [17]. Yoon et al [64] reported that the above risk can be drastically mitigated when farming activities take place 24 h after irrigation.…”
Section: Coliform Bacteriamentioning
confidence: 99%
“…Through QMRA of the E. coli concentration of paddy rice irrigation water, it was examined that the human health risk is very low when irrigating reclaimed wastewater. This means that additionally treated effluent after the regular WWTP processes meets the requirement for irrigation water [17]. However, when irrigating with treated wastewater diluted with stream water, the E. coli concentration exceeded the enteric disease risk value of 10´4, and this has been reported to cause infection to farmers [17].…”
Section: Coliform Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Os valores situaram-se na faixa de 4,00 a 10,00 mgP-PO4 coli inferiores a 10 -4 , em cenários de ingestão de 100 mg/dia de solo para adultos e 200 mg/dia para crianças. RHEE et al (2009), obtiveram um risco anual de infecção por este patógeno entre 10 -3 e 10 -5 em águas para irrigação, valores inferiores aos apresentados neste estudo, já ao final do tratamento primário. SEIDU et al (2008), constataram a concentração de ovos de Ascaris na água de irrigação na mesma ordem de magnitude descrita no presente estudo ~10 -2 .…”
Section: Discussionunclassified